2001
DOI: 10.1210/mend.15.8.0685
|View full text |Cite
|
Sign up to set email alerts
|

Members of the Kv1 and Kv2 Voltage-Dependent K+ Channel Families Regulate Insulin Secretion

Abstract: In pancreatic beta-cells, voltage-dependent K(+) (Kv) channels are potential mediators of repolarization, closure of Ca(2+) channels, and limitation of insulin secretion. The specific Kv channels expressed in beta-cells and their contribution to the delayed rectifier current and regulation of insulin secretion in these cells are unclear. High-level protein expression and mRNA transcripts for Kv1.4, 1.6, and 2.1 were detected in rat islets and insulinoma cells. Inhibition of these channels with tetraethylammoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(63 citation statements)
references
References 67 publications
4
59
0
Order By: Relevance
“…Reducing Kv current prolongs stimulus-induced depolarization of the ␤-cell plasma membrane and thereby amplifies insulin secretion (46,48). This could account for the observations that overexpression of iPLA 2 ␤ in insulinoma cells is associated with both amplified insulin secretion (21) and reduced Kv2.1 channel activity (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Reducing Kv current prolongs stimulus-induced depolarization of the ␤-cell plasma membrane and thereby amplifies insulin secretion (46,48). This could account for the observations that overexpression of iPLA 2 ␤ in insulinoma cells is associated with both amplified insulin secretion (21) and reduced Kv2.1 channel activity (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…To examine further effects of arachidonic acid on the activity of the Kv2.1 channel, which is the predominant delayed rectifier of ␤-cells (4,46), HEK cells expressing a Kv2.1-GFP construct (42) were studied (Fig. 1E) Arachidonic Acid Regulates Delayed Rectifier Currents in Both Rodent and Human Pancreatic Islet ␤-Cells-Because arachidonic acid affects the activity of Kv2.1 channels expressed in immortalized cell lines, we examined the possibility that similar effects would be observed with Kv currents in rodent and human primary ␤-cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous studies show that the general voltage-dependent K ϩ (Kv) 1 and Ca 2ϩ -sensitive voltage-dependent K ϩ (K Ca ) channel antagonist tetraethylammonium (TEA) augments membrane depolarization (12,13), Ca 2ϩ influx (14), and insulin secretion (13,15) in a glucose-dependent manner. Recently, we have reported that dominant-negative knockout of Kv2 channels reduced outward K ϩ currents by 60 -70% in rat ␤-cells and HIT-T15 insulinoma cells and caused a doubling of the insulin secretion response of rat islets to glucose (16). Kv2.1 likely plays this regulatory role because its protein expression is high in insulin-secreting cells (16,17), and mRNA for Kv2.2, the only other Kv2 family ␣-subunit known to form functional channels, could not be detected by reverse transcription-PCR (16).…”
mentioning
confidence: 99%
“…Recently, we have reported that dominant-negative knockout of Kv2 channels reduced outward K ϩ currents by 60 -70% in rat ␤-cells and HIT-T15 insulinoma cells and caused a doubling of the insulin secretion response of rat islets to glucose (16). Kv2.1 likely plays this regulatory role because its protein expression is high in insulin-secreting cells (16,17), and mRNA for Kv2.2, the only other Kv2 family ␣-subunit known to form functional channels, could not be detected by reverse transcription-PCR (16).…”
mentioning
confidence: 99%